Conceptual Integrated Science - Hewitt, Paul G., 1931-; Lyons, Suzanne A., ....-; Suchocki, John A., ....- (Harlow : Pearson Education Limited, 2014)
This introduction to the physical and life sciences emphasizes concepts over computation and treats equations as a guide to thinking so the reader can connect ideas. Conceptual Integrated Science covers physics, chemistry, earth science, astronomy, and biology at a level appropriate for non-science students. The conceptual approach relates science to everyday life, is personal and direct, deemphasizes jargon, and emphasizes central ideas. The conceptual ideas serve as the foundation supporting and integrating all the sciences.
1. About Science -PART I. Physics - 2. Describing Motion 3. Newton's Laws of Motion 4. Energy and Momentum 5. Gravity 6. Heat 7. Electricity and Magnetism 8. Waves—Sound and Light - PART II. Chemistry - 9. The Atom 10. Nuclear Physics 11. Investigating Matter 12. Chemical Bonds and Mixtures 13. Chemical Reactions 14. Organic Chemistry - PART III. Biology - 15. The Basic Unit of Life—The Cell 16. Genetics 17. The Evolution of Life 18. Biological Diversity 19. Human Biology I—Control and Development 20. Human Biology II—Care and Maintenance 21. Ecosystems and Environment - PART IV. Earth Science - 22. Plate Tectonics 23. Rocks and Minerals 24. Earth's Surface—Land and Water 25. Surface Processes 26. Weather 27. Environmental Geology - PART V. Astronomy - 27. The Solar System 28. The Universe
Keywords: Wetenschappen